Influence of thermal treatment on thermal properties of adamantane derivatives - Szewczyk, D.; Jeżowski, A.; Krivchikov, A.I.; Tamarit, J.Ll. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
Heat transport mechanisms present in 2-adamantanone and 1-cyanoadamantane crystals were investigated in a broad temperature range. To characterize scattering processes, thermal conductivity and heat capacity measurements were carried out. A particular care was paid to the cooling rate of specimen which influenced the thermal history of the samples. The experimental results led to a conclusion that under slow cooling the thermal conductivity reaches the highest values and resembles the behavior of ordered molecular crystals. As for fast cooling, the “quenching” resulted in changes in both the structure and the temperature dependence of the thermal conductivity, the latter resembling that of amorphous solids. In heat capacity measurements the thermal history made on samples did not reflect the preliminary findings known from thermal conductivity results, which could imply that the observed mechanisms are more complex.